Descriptions of New Species of Leucotrichiinae (Trichoptera: Hydroptilidae) from Brazil - Robin E. Thomson (Psyche: A Journal of Entomology)
Two new species of Hydroptilidae (Trichoptera) from Brazil are described: Betrichia alibrachia sp. n. and Leucotrichia bicornuta sp.n. Both genera are members of the subfamily Leucotrichiinae. Illustrations of male genitalia are provided with each description. These additions bring the total world fauna of Betrichia to 9 species and Leucotrichia to 29 species.